PERKEMBANGAN ANAK DALAM TINJAUAN SOSIAL - Rustina, Rustina (Pusat Studi Gender dan Anak, IAIN Palu, 2018)
The development of the social conditions of children has a considerable influence in increasing their self-reliance, enthusiasm or motivation in learning. Considering the analysis in this paper shows that the unpleasant social conditions experienced by children trigger negative thought patterns. In this case the head of the Foundation and the administrators continue to strive, therefore the community or family environment has a role in providing support in the form of attention, affection, guidance and also trying to develop abilities and shape the character of children in interacting in realizing values - karima moral values.Thus it is obtained that is the social condition of each child has a strong soul in facing life challenges so that the child does not make his social condition an obstacle but makes it a challenge to achieve success.